Pengaruh Job Description, Job Specification, Standar Kerja Dan Lingkungan Kerja Terhadap Produktivitas Karyawan Studi Pada Balai Produksi Dan Informasi Audio Visual Kota Surabaya - Abd. Wahed; Abdul Kodir Djaelani; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2021)
AbstractPurpose of this study was to determine and analyze the effect of job description, work specification and work environment on employee productivity at the Surabaya City Audio Visual Information and Production Center. To find out and analyze job describtions on employee productivity at the Surabaya City Audio Visual Information and Production Center. To find out and analyze work standards on employee productivity at the Surabaya City Audio Visual Information and Production Center. To find out and analyze the work environment on employee productivity at the Surabaya City Audio Visual Information and Production Center. This type of research uses Explanatory Reaserch. This research was conducted at the Surabaya City Audio Visual Information and Production Center which is located at Jl. Gayungan Kebonsari no-50, Surabaya, East Java. The population in this study were employees of the Surabaya City Audio Visual Information and Production Center as many as 40 people. The results of this study indicate that the job describtion, job specifications, work standards and work environment simultaneously have a significant effect on employee productivity. Keywords: Job description, Job Specification, Work Standards and Work Environment